ASSOCIATION BETWEEN OBESITY PARAMETERS AND POOR OUTCOMES IN HOSPITALIZED PATIENTS WITH CONFIRMED MILD TO MODERATE COVID-19 - Barus, Nadya; Kurniawan, Farid; Sinto, Robert; Mansjoer, Arif; Tahapary, Dicky; Wafa, Syahidatul; Rosana, Martha; Pradnjaparamita, Tika; Kartika, Rona (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE This study aims to assess visceral fat values, waist circumference (WC), body mass index (BMI), and body fat percentage for their ability to predict poor outcomes during COVID-19 patients’ hospitalization. METHODOLOGY This research has been approved by an ethical committee. This study is a prospective cohort of mild-moderate COVID-19 cases at Cipto Mangunkusumo Hospital who were hospitalized from December 2020 to March 2021. Patients were examined for visceral fat values and body fat percentage using a bioimpedance analyzer (BIA), WC and BMI at admission. Multivariate logistic regression analysis was performed to assess visceral fat, body mass percentage, BMI, and WC abilities in predicting poor composite outcomes of ARDS and mortality. RESULTS Two hundred and sixty-one patients were included. Visceral fat (RR 1.12 [95% CI 1.03-1.21], p=0.005) and waist circumference (RR 1.05 [95% CI 1.02-1.08], p=0.11) were associated with poor outcomes. Neither body percentage (RR 0.99 [95% CI 0.96-1.02], p=0.72) nor BMI (RR 1.05 [95% CI 0.99-1.12], p=0.11) were associated with poor outcomes. Based on multivariate logistic regression, WC was statistically significant as an independent risk factor influencing poor outcomes in COVID-19 patients (RR 1.04 [95% CI 1.01-1.08], p=0.003), which can be interpreted that each 1 cm increase in waist circumference was associated with a 4% increased risk of composite poor outcomes. CONCLUSION Visceral obesity parameters were significantly associated with poor outcomes in mild to moderate COVID-19 cases.